Practicality Assessment of Student Worksheets for SMP Physics Learning on the Traditional Culture-Based Equipment - Fakhruddin Z, Fakhruddin Z; Halim, Lilia; Mohd Meerah, T. Subahan (FKIP-Universitas Riau, 2017)
The purpose of this study is to examine the practicality of StudentWorksheets (LKS) physics learning at junior high school (SMP) forvalidated traditional culture-based tools. The topic of the LKS is simplemachine. The method used in the study is a research and development. Theresearch was conducted at the Junior High School in Pekanbaru which thedata source was from three science teachers and thirty students of class VIII.The LKS practicalities data was obtained through questionnairespracticalities of the device which was given to teachers and students. Theanalysis of the data used descriptive analysis that is to categorize the averagescore on learning process. Based on the analysis of the data, the practicalityof the LKS has an average with the excellent category for all aspects. Thisshows the LKS of physics learning at junior high school based on thetraditional culture equipment on the topic of simple machine practical can beused as a medium of learning physics at junior high school.